Main and Moderating Effects of an Online Transition Curriculum on Career Readiness. (August 2020) - Lombardi, Allison; Rifenbark, Graham; Tarconish, Emily; Volk, Daniel; Monahan, Jessica; Buck, Andrew; Izzo, Margo; Murray, Alexa
In this study, students with and without disabilities ( n = 816) in general and special education settings in Grades 9 through 12 were participants in a quasi-experimental design to examine the main effects of an online curriculum intervention with transition-related content on career readiness. Setting and teacher characteristics were examined for moderating effects. Results showed a main effect across settings (general and special education, self-contained, resource rooms) as well as differentiating effects based on teacher fidelity and the number of lessons taught. Implications are discussed with regard to the need for further examination of these contextual factors in high schools so all students, with and without disabilities, are provided career readiness opportunities.